School Inclusion Law in Chile: management challenges for subsidized private establishments (Práxis Educativa, 2023)
Chile has one of the most segregated social systems in the world, the same is true of its school system. In this context, the so-called “School Inclusion Law” was promulgated in 2015. This text analyzes the scope of the implementation of this policy for key school agents in the Maule region (Chile), beginning by characterizing the sector called "private-subsidized", and then synoptically describing the policy. The work methodology is qualitative with an exploratory scope and was implemented through a semi-structured interview with directors of subsidized private schools, owners of establishments and regional ministerial secretaries of education. The results agree that it is necessary to deal with essential matters such as more work with management actors, teachers and parents, observing the need to reinforce basic principles of the law: inclusion and equal educational opportunities and parents, noting the need to reinforce the basic principles of the law: inclusion and equal educational opportunities.Keywords: School inclusion. Private-subsidised education. Educational actors.